Bond License in Readymade Garment Industry: A Study of Sublime Greentex Limited - Hossain, Md. Shanayaz (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Post Graduate Diploma in Knitwear Industry Management, 2021.